“Revisión de los contratos colectivos en relación al mandato 08 referente a la intangibilidad de los derechos del trabajador” - Freire Amaya, Mayra Alejandra (2015)
The progress of societies throughout history has always been based on work, which was initially carried out with abuses of the worker, which was often thanks to inhuman rulers and employers; with this unbearable situation that the workers lived; I force these to seek in the union the strength that they lacked individually to demand improvements, in this way the first workers' associations appear, which gradually became a right of association and collective bargaining, perfecting itself in the collective contract, recognized in the International Labor Organization, in addition to principles such as; the inalienability and intangibility of the worker's rights. However, with all these implementations for the benefit of the working class, workers' rights are still being violated today, which is why it is necessary to carry out an investigative study in which it can be determined which rights and principles are violated.